A three-step support strategy for relatives of patients dying in the intensive care unit: a cluster randomised trial. Issue 10325 (12th February 2022) - Kentish-Barnes, Nancy; Chevret, Sylvie; Valade, Sandrine; Jaber, Samir; Kerhuel, Lionel; Guisset, Olivier; Martin, Maëlle; Mazaud, Amélie; Papazian, Laurent; Argaud, Laurent; Demoule, Alexandre; Schnell, David; et al.
Summary: Background: In relatives of patients dying in intensive care units (ICUs), inadequate team support can increase the prevalence of prolonged grief and other psychological harm. We aimed to evaluate whether a proactive communication and support intervention would improve relatives' outcomes. Methods: We undertook a prospective, multicentre, cluster randomised controlled trial in 34 ICUs in France, to compare standard care with a physician-driven, nurse-aided, three-step support strategy for families throughout the dying process, following a decision to withdraw or withhold life support. Inclusion criteria were relatives of patients older than 18 years with an ICU length of stay 2 days or longer. Participating ICUs were randomly assigned (1:1 ratio) into an intervention cluster and a control cluster. The randomisation scheme was generated centrally by a statistician not otherwise involved in the study, using permutation blocks of non-released size. In the intervention group, three meetings were held with relatives: a family conference to prepare the relatives for the imminent death, an ICU-room visit to provide active support, and a meeting after the patient's death to offer condolences and closure. ICUs randomly assigned to the control group applied their best standard of care in terms of support and communication with relatives of dying patients. The primary endpoint was the proportion of relatives with prolonged grief (measured with PG-13, score ≥30) 6 months after the death. Analysis was by intention to treat, with the bereaved relatives as the unit of observation. The study is registered with ClinicalTrials.gov, NCT02955992 . Findings: Between Feb 23, 2017, and Oct 8, 2019, we enrolled 484 relatives of ICU patients to the intervention group and 391 to the control group. 379 (78%) relatives in the intervention group and 309 (79%) in the control group completed the 6-month interview to measure the primary endpoint. The intervention significantly reduced the number of relatives with prolonged grief symptoms (66 [21%] vs 57 [15%]; p=0·035) and the median PG-13 score was significantly lower in the intervention group than in the control group (19 [IQR 14–26] vs 21 [15–29], mean difference 2·5, 95% CI 1·04–3·95). Interpretation: Among relatives of patients dying in the ICU, a physician-driven, nurse-aided, three-step support strategy significantly reduced prolonged grief symptoms. Funding: French Ministry of Health